Parties to Offences under the Canadian Crimes against Humanity and War Crimes Act : an Analysis of Principal Liability and Complicity - Lafontaine, Fannie (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2009)
The Crimes against Humanity and War Crimes Act presents an interesting mosaic of law applicable to the domestic prosecution of genocide, crimes against humanity and war crimes. The definitions of offences refer essentially to international law, whereas the available defences, justifications and excuses are those of both Canadian law and international law, and the modes of participation in offences are exclusively those of Canadian law. This raises the question of the relevance and effectiveness of the legislative choice to apply domestic law to the principles of liability for international crimes. The present study offers a preliminary and limited analysis of certain modes of participation in offences provided for by the Act, namely perpetration and complicity pursuant to section 21 of the Criminal Code. This analysis aims at assessing, in light of the principles developed in international criminal law with respect to individual responsibility, whether and how Canadian law may be adapted to the particular — collective — nature of international crimes.